Sexism and misogyny as traits of police culture: Problems, red flags and solutions - Turner, Allison (International journal of police science & management, 2024)
The aim of this article is to utilise pre-existing literature to explore the problems of misogyny and sexism currently found to be operating within the police service, and to provide recommendations around reform. This article analyses problems associated with sexism and misogyny at a time of media scrutiny following the Baroness Casey Review of the Metropolitan Police culture, which identifies these concepts as an institutional problem that can impact upon female police officers and women in general. The article begins by highlighting the importance of understanding the differences between sexism and misogyny and then reviews potential strategies towards police reform. These changes include a review of policy and law, use of education, leadership changes, reform to the Police Complaints and Discipline system, male peer support and more-effective whistleblowing processes. The article concludes by establishing that all strategies are worthy of consideration to reform a negative police culture. It also acknowledges that failures to respond to the challenges of dealing with misogyny and sexism effectively, will result in the strengthening of a police culture that continues to damage the police’s reputation and public trust and which will consequently affect all who are victim and witness to this behaviour.